Comportamiento agronómico de cinco hortalizas de raíz con tres tipos de abonos orgánicos en la hacienda Tecnilandia – Quevedo. - Palma Méndez, Karina Vanessa (2013)
This research was carried out in the Hacienda Tecnilandia located at kilometre 11 Via the joint right margin; belonging to the Canton Quevedo, Los Ríos province. More a witness factorial was used a complete block design (DBCA) randomly in accordance with five vegetables with three organic fertilizers and three repetitions. The results were: in the corresponding to green onion in the variable height of plant assessed at 90 days can be seen in table 6 greater plant height was given treatment Humus de lombriz with 52,88 cm. In relation to number of leaves Jacinto Humus de lombriz in water treatment achieved the highest average with 50.80 leaves, for the number of stems the control treatment obtained the largest number of stems with 16.56 stems; for the variable length of stem treatment Humus de lombriz with 9.47 cm and in reference to the stem diameter treatment Jacinto Humus de lombriz in water with 2.94 cm in diameter. For the weight per treatment Humus de lombriz water hyacinth achieved greater weight with 972.33 g, in the same way the same express treatment the highest yield per hectare with 9.72 t ha-1. In sugar beet for variable height of 30, 45 and 60dias plant Humus de lombriz treatment achieved the highest average with 23.27; 37.10 and 33.80 cm. For behavior agronomico Humus de lombriz treatment achieved the highest average in number of leaves at 30 days (8.98); Number of leaves at harvest (5.82); diameter of fruit within 60 days with 9.69 cm; weight 75 days with 1576.33 g and performance with 15.77 t ha-1. In plant height of red onion to 90 days shown in table 10 Humus de lombriz treatment achieved the highest average with 48.75 cm. treatment Humus de lombriz presents the best averages in number of days to harvest with 12.17 leaves; leaves the harvest with 7.75; diameter of root with 5.77 cm; weight with 678.83 g and performance with 6.79 t ha-1. In height the control treatment reached the highest average with 37.95 cm, in number of leaves at 10 days treatment Jacinto de Agua resulted with the best average with 11.21 leaves. Treatment carrot + humus de lombriz obtained the highest mean plant height at 90 days with 54.54 cm, number of leaves and bulb diameter 10.22 to 20.47 cm. Carrot + treatment + humus de lombriz water hyacinth took top bulb averages along with 8.00 cm, fruit weight and performance with 292.78 2.93 t ha-1. In regard to the control treatment radish obtained higher average plant height of 37.95, radish treatment + water hyacinth had the best averages in number of leaves at 10 days and final leaf number 11.21 and 8.71 respectively, while that treatment of radish + humus de lombriz + water hyacinth obtained the best average root diameter, fruit weight and performance with 4.11 - 449.67 and 4.50 t ha-1 respectively.